Mental Health Problems in Girls Who Committed Sexual Offenses: Similarities and Differences Compared to Girls With Non-sex Offenses and Boys With Sex Offenses - Manetsch, Madleina; Nelson Aguiar, Rebecca J.; Hermann, Daniel; van der Put, Claudia; Grisso, Thomas; Boonmann, Cyril (Frontiers in Psychology, 2021)
Female juvenile offenders have only recently shifted into the focus of research. Moreover, a specific subgroup, female juveniles who sexually offended (JSOs) are greatly overlooked. Therefore, there is a dearth of knowledge regarding the characteristics of female JSOs. The aim of the current study is to explore mental health problems (MHP) of female JSOs in more detail. Moreover, we compared their mental health with female juveniles who committed non-sexual offenses (JNSOs) and male JSOs. The sample comprised 33 female JSOs (Mean age 14.5, SD 1.8), 33 age matched female JNSOs and 33 age-matched male JSOs. We used the Massachusetts Youth Screening Instrument-Version 2 (MAYSI-2) to examine MHP. Although both internalizing and externalizing MHP were not uncommon in female JSOs, they reported fewer problems than female JNSOs. No differences were found between female and male JSOs. With regard to their mental health profile, female JSOs resemble male JSOs more than female JNSOs. These results should be taken into account in the assessment and treatment of this group. However, more research is needed.